Attitudes towards to sexuality among older people: a qualitative research - Alves, Patrícia (2016)
Sexuality is an important component of human being and contributes to the quality of life. Sexual activity dependa on altitudes toward sexuality. Although this is an important issue, the research on attitudes toward sexuatity among older people hás been a neglected topic. Objectives: To understand altitudes towards sexuality among older people and to assess the relationship between sociodemographic factors and such attitudes.Methods: This cross-sectíonal study was conducted on 35 community-dwelltng older individuais (> 65 years old; 66% were men). Data collectíon was based on a questionnaire whtch includes three components: (1) Questíons on sociodemographic characteristícs; (2) A 13-item scale assessment of attitudes toward to sexualtty (SAATS) scored from O to 52, being highervalues related with positive attítudes; and (3) an open question "in your opinton what is sexuality?". Results: In this sample 40% of participants (n = 14) reported that there is no sexuality among older people. For the whole sample, the mean score of SAATS and respective standard deviatíon (± SD) was 28. 9 (± 6. 63). There were no differences in the mean score of SAATS by gender, but such score was lower among oldest people (p = 0. 006), among individuais reporting less schooling years (p = 0. 001) and among those with no companion (p = 0. 012). In regards to the qualitatíve analysis of the open question, the main answers obtained fali into the affectíve dimension, with the majority of partidpants reporting that sexuality is "lave", "respect" and "tenderness". Conclusions: Oldest people, those with lower educatíon levei and those with no companion presenting more negative attítudes towards to sexuality. Among older people sexuality is manly based on the affective dimension.